2018
DOI: 10.1029/2018jb016121
|View full text |Cite
|
Sign up to set email alerts
|

Transient Electromagnetic Surveys for the Determination of Talik Depth and Geometry Beneath Thermokarst Lakes

Abstract: Thermokarst lakes are prevalent in Arctic coastal lowland regions and sublake permafrost degradation and talik development contributes to greenhouse gas emissions by tapping the large permafrost carbon pool. Whereas lateral thermokarst lake expansion is readily apparent through remote sensing and shoreline measurements, sublake thawed sediment conditions and talik growth are difficult to measure. Here we combine transient electromagnetic surveys with thermal modeling, backed up by measured permafrost propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 79 publications
(134 reference statements)
2
35
0
1
Order By: Relevance
“…In a future study, a larger NMR loop size could improve the ability to discern the talik base, but it is important to keep in mind that the depth of investigation with large loops can be limited in very high latitudes by the high magnetic field inclination (Parsekian et al, ). It is possible that deeper imaging the talik base could also be accomplished using other deeper‐penetrating geophysical methods such as transient electromagnetics (Creighton et al, ) or airborne electromagnetics (Minsley et al, ), though we hypothesize that such surveys would have limited success at the Kuparuk site, where electrically resistive subsurface conditions observed during initial testing indicated that multifrequency EM surveys would likely yield little useful information. Direct current electrical resistivity methods (e.g., Minsley et al, ; Sjöberg et al, ; Yoshikawa & Hinzman, ) would be more suited to the resistive subsurface materials at the Kuparuk site and could potentially provide useful supporting information on talik thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In a future study, a larger NMR loop size could improve the ability to discern the talik base, but it is important to keep in mind that the depth of investigation with large loops can be limited in very high latitudes by the high magnetic field inclination (Parsekian et al, ). It is possible that deeper imaging the talik base could also be accomplished using other deeper‐penetrating geophysical methods such as transient electromagnetics (Creighton et al, ) or airborne electromagnetics (Minsley et al, ), though we hypothesize that such surveys would have limited success at the Kuparuk site, where electrically resistive subsurface conditions observed during initial testing indicated that multifrequency EM surveys would likely yield little useful information. Direct current electrical resistivity methods (e.g., Minsley et al, ; Sjöberg et al, ; Yoshikawa & Hinzman, ) would be more suited to the resistive subsurface materials at the Kuparuk site and could potentially provide useful supporting information on talik thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The modeled talik thickness after 5,000 years was 107 m, which is comparable to other studies. On the Alaskan coastal plain, thermokarst taliks over 90 m deep have been interpreted from TEM data (Creighton et al., 2018), and a talik 95 m deep was also interpreted from shallow seismics in the Lena Delta in Siberia (Schwamborn et al., 2002). In the initial phase of thermokarst development, the lake was completely isolated from Tiksi Bay (Figure 9a).…”
Section: Discussionmentioning
confidence: 99%
“…The total thaw depth (talik depth ∼32 m, altitude difference between lake and Yedoma uplands ∼20 m) of ∼52 m is relatively shallow for 8000 years of thermokarst development (M. Angelopoulos, personal communication, 2020). Previous talik modeling studies of Alaskan thermokarst lakes showed faster talik growth rates for lakes in North America (e.g., Ling and Zhang, 2003;West and Plug, 2008;Kessler et al, 2012;Creighton et al, 2018). However, talik growth could be slowed by characteristics of Siberian Yedoma, such as its higher ice volume in these sediments or the presence of bedfast ice during an extended shallow lake phase (<2 m).…”
Section: Unit Iii/unit a -Yedoma Deposition Under Cold-dry Conditionsmentioning
confidence: 94%